Development of web-based French language learning media on Réception Écrite courses - PRAMUNIATI, I (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The aims of this study are to develop a web-based learning media, explaining the quality of web-based learning media. The method that is used in this study is research and development (R & D) a method that is oriented to 30 college students studying at the French Language Education Program of Study, Language and Art Faculty at University of Negeri Medan as a sample. The results are: (1) a web-based learning media has been developed successfully; (2) based on the validation result done by media learning expert, this media learning development result is on a good category.RESUMEN Los objetivos de este estudio son desarrollar un medio de aprendizaje basado en la web, explicando la calidad de los medios de aprendizaje. El método utilizado en este estudio es la investigación y desarrollo ( I & D) como un método que se orienta, contando con 30 estudiantes universitarios como muestra del programa del idioma Francés de la Facultad de Arte y Lenguaje de la Universidad Negeri Medan, Los resultados son: (1) se ha desarrollado con éxito un medio de aprendizaje basado en la web; (2) basado en el resultado de validación realizado por un experto en aprendizaje de medios, este resultado de desarrollo de aprendizaje de medios está en una buena categoría.